Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan dan Aset Pajak Tangguhan terhadap Manajemen Laba Dimoderasi Leverage - Helenia Fatimah Sari; Purwantoro Purwantoro; Enny Susilowati Mardjono; Agung Prajanto (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the effects of tax planning, deferred tax expenses, and deferred tax assets on earnings management, with leverage serving as a moderating variable. The research focuses on the Consumer Non-Cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2025 period. Employing a quantitative approach with a causal design, the study utilized purposive sampling to select 26 sample companies. Data analysis was conducted using Multiple Linear Regression and Moderated Regression Analysis (MRA) through SPSS software. The results indicate that tax planning, deferred tax expenses, and deferred tax assets do not have a significant effect on earnings management. Furthermore, leverage was not proven to moderate the relationship between the independent variables and earnings management. The low coefficient of determination suggests that the research model has limited capability in explaining variations in earnings management. These findings contribute to the understanding that tax policies and funding structures may not yet serve as primary indicators for detecting earnings management practices, highlighting the need for investors, management, and regulators to consider other factors.